Kontribusi Gereja Masehi Injili di Minahasa (GMIM) Eben Haezer Buntong dalam Menangani Krisis Ekologi di Tateli - Nainggolan, Alon Mandimpu; Tendean, Joshua Enrico; Kasiahe, Octaniel; Heydemans, Nency Aprilia (Institut Agama Kristen Negeri Manado, 2023)
This article aims to analyze and describe the involvement of the Evangelical Christian Church in Minahasa (GMIM) Eben Haezer Buntong in caring for the earth, especially in dealing with the ecological crisis in the Tateli region. The method used is qualitative descriptive by utilizing observation and interviews as data collection techniques. It becomes a church calling to care for, preserve and be responsible for this earth. Man is the image and likeness of God, assigned as a caretaker of the earth and not as a destroyer of the earth. Preserving the environment is the responsibility of everyone, parties and organizations, especially the church. GMIM's example, which has formulated and demonstrated according to its capacity the importance of maintaining harmony in human and environmental relations and socializing congregation members to care about their environment should be an inspiration. Through this research it was found that GMIM Eben Haezer Buntong has contributed to the maintenance of the earth through congregational programs such as the youth cleaning program once every three months, men's work for fathers, women's work for mothers, clean Friday, and planting trees. This study recommends not cutting trees carelessly and maintaining the quality of the springs.